Mise en place d'un cours de lecture-compréhension en français aux 2e et 3e cycles universitaires en Argentine : le cas de la FaHCE. Une analyse ethnographique - Spoto Zabala, Daniela (2021)
After conducting an analysis of needs among university students, especially at the FaHCE, there was a request concerning French reading of postgraduate texts. Based on this observation, a reading comprehension course in French was launched as part of this action research. Designed according to a FOS/FOU approach, it targeted a heterogeneous audience of allophone university students. From an ethnographic perspective, the aim of this work was, on the one hand, to observe the most specific aspects allowing to design a relevant pedagogical tool to meet the demand of Argentinian students; on the other hand, to analyse the data obtained -through the proposed course- in order to identify and characterize the strategies deployed by the learner-readers. Key concepts are developed such as: socio?discursive interactionism, reading strategies, global reading, word for word translation, among others.